Understanding the Fear of Crime and Perceived Risk Across Immigrant Generations: Does the Quality of Social Ties Matter? - Yuan, Yue (Crime & delinquency, 2024)
The current study examines the relationships between immigration, social ties, and perceptions of safety. We estimated immigrant generation by race/ethnicity interactions to uncover unique patterns across subpopulations of immigrants while controlling for important neighborhood contextual factors. Immigrant generation was negatively associated with feelings of fear. First-generation Asian immigrants reported the greatest level of fear in the sample. High-quality social ties were negatively associated with fear of crime, while the number of social ties was unrelated to fear. Results suggest first-generation immigrants are in a precarious position in society with respect to feeling safe in their neighborhoods. Local officials should seek ways to provide accurate messaging on the threat of victimization in immigrant communities.